The performance of palm oil boiler stones (POBS) and quarry dust as partially sand replacement in mortar - Balkish, Muhammad Ali (2012)
Recently there has been a growing trend towards the use of supplementary materials, whether natural, waste or by-product because of ecological, economical and diversified product quality reasons. The compressive strength of mortar is an important property because it usually gives an overall picture of the quality of mortar. Mortar strength development is determined not only by the water-cement ratio but also influenced by many other factor such as the admixtures used and curing condition. One of the many challenges of research work in engineering material is to improve the material in different ways to obtain a better product. The palm oil boiler stone (POBS) and quarry dust are new waste materials and abundantly available has the potential as a replacement for sand in the production of mortar. This study investigates the effects of substitution of POBS and also quarry dust towards the physical properties of mortar which consist of workability and compressive strength. Three types of samples were prepared with the constant water/cement ratio (w/c) of 0.55 and POBS and quarry dust that contains 5%, 10% and 15% in mortar. A total of 63 cube sample specimens 50 mm x 50 mm x 50 mm were prepared for standard testing. The tests that were conducted are flow table test and compression test at curing age of 7, 28 and 60 days. The study also shows that the substitution of quarry dust POBS and improve the workability and strength of mortar until 38.24% which is the highest result for POBS and 17.34% for quarry dust at 28 days. The result of this study indicates that the substitution of POBS and quarry dust aggregates increases the workability and strength of mortar.